CREATING NEW LEARNING PLATFORMS ON A TECHNOLOGICAL FRAMEWORK (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores the importance of technological infrastructure in creating modern educational platforms. It examines theapproaches used in designing, developing, and integrating new learning platforms. Emphasis is placed on enhancing student engagement through technological tools and providing interactive learning opportunities. The article also providesrecommendations for increasing the efficiency of the educational process using contemporary platforms